THE USE OF STATISTICAL METHODS IN ANALYZING ACCOUNTING DATA (Ustozlar uchun, 2025)
AbstractThis research explores how statistical methods are applied in analyzing accounting data to enhance accuracy, reliability, and decision-making. The integration of statistics into accounting processes helps identify financial trends, detect irregularities, and predict future performance. Using a qualitative research approach, the article reviews relevant literature and discusses how tools such as correlation, regression, and time-series analysis support accountants in evaluating financial statements. Findings show that the use of statistical techniques improves data quality, strengthens auditing, and supports evidence-based financial decisions.